Penguatan Kolaborasi Guru SMK melalui Outbound Training: Perspektif Experiential Learning - Dinis Cahyaningrum; Ni Wayan Adelia Mutiara Asri; Isra Dewi Kuntary Ibrahim; Muhammad Najib Roodhi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the effectiveness of experiential learning-based outbound training in strengthening teacher collaboration in vocational high schools (SMK). Collaboration is viewed as a crucial foundation for developing a collective work culture and improving the quality of teaching and learning. The research employed a mixed-method approach with a sequential exploratory design, involving 78 teachers from three departments at SMK GS through pretest–posttest, participatory observation, and in-depth interviews. The results showed an average increase of 49.4% in collaboration scores, with the highest improvement in the group processing aspect, indicating teachers’ enhanced ability to evaluate and manage teamwork reflectively. Qualitative data supported these findings, revealing changes in teachers’ mindsets and collaborative behavior across departments. The study concludes that experiential learning-based outbound training is an effective transformational learning strategy for strengthening teacher collaboration and fostering a professional culture in vocational education settings.